Indeterminacy: an investigation into the Soritical and semantical paradoxes - Bacon, AJ (2012)
According to orthodoxy the study of the Soritical and semantical paradoxes belongs to the domain of the philosophy of language. To solve these paradoxes we need to investigate the nature of words like `heap' and `true.' In this thesis I criticise linguistic explanations of the state of ignorance we find ourselves in when confronted with indeterminate cases and develop a classical non-linguistic theory of indeterminacy in its stead. The view places the study of vagueness and indeterminacy squarely in epistemological terms, situating it within a theory of rational propositional attitudes. The resulting view is applied to a number of problems in the philosophy of vagueness and the semantic paradoxes.